Efecto del tratamiento con suero autólogo en la evolución de la queratoconjuntivitis sicca en una paciente con síndrome de Sjögren asociado a lupus eritematoso sistémico: Un reporte de caso (2024)
Sjögren's syndrome (SS) is a chronic inflammatory autoimmune disorder which mainly affects the exocrine glands, such as the lacrimal glands, making it one of the causes of Dry Eye Disease (DED).